Individual Investors’ Risk Behaviour and Share Trading Frequency: Evidence from Dar es Salaam Stock Exchange - Christina Alfred Mwakabumbe; Sylvia Temu; Isaac Kazungu (Journal of Accounting Research, Organization and Economics, 2022)
Objective – This paper examines the risk behaviour of individual investors in the Dar es Salaam Stock Exchange (DSE), Tanzania. Furthermore, it aims to analyse how risk behaviour variables influence individuals' trading frequency of shares at the DSE.Design/methodology –The study uses cross-section data from a structured questionnaire distributed to 200 individual investors selected with a snowball sampling procedure. It further used descriptive statistics and multinomial logistic regression (MLR) to analyse the risk behaviour of individual investors and their impact on share trading frequency.Results – The study reveals that share prices, investment experience, and amount of funds invested depict the risk aversion behaviour of individual investors and thus influence their share trading frequency at DSE. However, individuals’ risk perception did not significantly influence share trading frequency.Research limitations/implications –The study used individual investors to assess risk behaviour in trading frequency. However, individuals have limited risk awareness and analysis knowledge and use brokers and financial analysts.Novelty/Originality –Individual investors' risk behaviour in relation to share trading at DSE received attention for the first time in this paper. The study proposes to DSE improve policies and training programs relating to individuals trading and risk management to stimulate active share trading among individual participants in exchange for improved liquidity and contribution to economic growth.